SV40 seroprevalence in two Latin American countries involved in field trials of candidate oral poliovaccines. Issue 6 (June 2019) - Wong, Connie; Zhang, Shaojie; Adam, Ervin; Paszat, Lawrence; Butel, Janet S.
Highlights: Polyomavirus SV40 was an unrecognized contaminant of early poliovaccines administered to millions. People in Latin America where vaccine trials took place often have SV40 neutralizing antibodies. Evidence indicates that SV40 is causing human infections today. Results of studies of SV40 infections in humans depend on the populations analyzed. Summary: Objectives: This study sought to determine SV40 seroprevalence in residents of two Latin American countries, Colombia and Nicaragua, which were sites of prelicensure oral poliovaccine (OPV) trials. Methods: Archival sera were tested for SV40 neutralizing antibody using a virus-specific plaque-reduction assay. Samples included 517 sera from Colombia and 149 sera from Nicaragua. Results: Overall SV40 seroprevalence was 22.8% for Colombian subjects and 12.8% for Nicaraguans. Subgroups of Colombian subjects ranged in frequency of SV40 seropositivity from 10.0% to 38.6%. Birth cohorts both older and younger than the age cohort that contained potential OPV vaccinees from both countries had SV40 antibodies. Gender and ethnicity had no significant effects on SV40 seropositivity. Conclusions: Inhabitants of both Colombia and Nicaragua had detectable SV40 neutralizing antibody, including those of ages presumably not recipients of potentially SV40-contaminated OPV. This observation provides support for the concept that transmission of SV40 human infections can occur. Frequency of SV40 antibody positivity was elevated over that reported for the US where there was limited use of contaminated OPV. This investigation indicates also that study results of SV40 infections in humans will reflect whether subject populations had probable exposures to contaminated poliovaccines and to environmental conditions favoring cycles of viral transmission.